If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3p+13=-29
We simplify the equation to the form, which is simple to understand
3p+13=-29
We move all terms containing p to the left and all other terms to the right.
+3p=-29-13
We simplify left and right side of the equation.
+3p=-42
We divide both sides of the equation by 3 to get p.
p=-14
| 8x-3=2(x+15) | | 1/10(x+3)=1/4(2-x) | | 4m-3+7m=30 | | 2(x-5)+3=11 | | x+0.8=0.4(x+5) | | 10+2x=50 | | (7x+9)=(6+10x) | | 4x+1.3=6x-1.1 | | 2x-72+x-15=11 | | 2a^2-3a+5=0 | | 2x-1080=2x-11 | | 4(x-4)+2x=6(x+5)-46 | | 8(x-3)=4 | | x-9=-3x-9 | | 2x-72+x-15=2x-11 | | -7(x-4)=21 | | x-15=2x-72 | | 10-2x=50 | | x/4+4/5=5/12 | | 7x-3+3x=9 | | 5(x+7)=4(x-6)+x | | 7x-3+9=3x | | 7x-3=3x | | 6(-7)+x=7(x-7)+7 | | 2x+11=19-2x | | 20(x+3)=4(15+5x) | | 2x-5/8+x=2x+5/2+2 | | -3(2m-9)+7(m-4)=12-9 | | x/2-4=2 | | -6x-x=0 | | x^4-3x^2-10= | | -2(x+3)=18 |